Consumer Preferences and Acceptance of Meat Products - Garmyn, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue "Consumer Preferences and Acceptance of Meat Products" demonstrates that the value of different palatability traits has evolved over time. Moreover, consumer acceptance and preference are not solely determined by the inputs of the meat itself, but can also be influenced by various demographic factors. In addition, consumers' views of meat products vary regionally and by species.